Pengembangan Hybrid Tepung Ubi Jalar Kaya Antioksidan - Sefanadia Putri (Politeknik Kesehatan Tanjung Karang, 2019)
Sweet potato is one type of tubers found in Indonesia. Hybrid of sweet potato flour is obtained from the modification of the processing by fermentation using lactic acid bacteria. The purpose of this study was to determine the nutritional and antioxidant content of various types of hybrid sweet potato flour. This research is an experimental laboratory with a true-experiment design. The experiment was arranged in a complete randomized block design (RCB) with three replications. The treatments are 6 types of sweet potatoes which include purple sweet potato Var.Antin 1, purple sweet potato val.local, white sweet potato, orange sweet potato, Japanese purple sweet potato Var.Ayamurasaki and cilembu sweet potato. The study included the fermentation process using lactic acid bacteria (Acetobacter xylinum) addition concentration of 5%, siege, analysis of nutrient content (water, ash, protein, fat, fiber and carbohydrates) and antioxidant activity of various types of hybrid sweet potato flour. The results showed that various types of hybrid sweet potato flour significantly affect the nutritional content which includes water content, ash content, fat content, protein content, fiber content and total carbohydrate. The result of antioxidant activity in various types of hybrid sweet potato flour after fermentation treatment in a concentration of 5% Acetobacter xylinum ranged from 29,383-53.7929%. The lowest value obtained at cilembu hybrid sweet potato flour and the highest value was obtained from the Japanese hybrid sweet potato flour var.Ayamurasaki.